#Patriarchykapackup: mediating sexual discourse and the casteless feminist subject in Indian performance poetry. Issue 3 (3rd July 2022) - Rao, Pallavi
ABSTRACT: Exploring the formations of gender, caste, sexuality, and class in India, this article examines the seemingly casteless discursive and material fields in the poetry of upper-caste female slam poets performed live in Mumbai and hosted on YouTube channels. I approach these texts as a form of mediated erotics occupying media sites contentiously marked as obscene and pornographic by the state while nuancing how these mediums harness language, sound, and speech for confessional sexual articulations. Studying these poets' discursive strategies towards pleasure and desire and their digital circulation on a transnational scale, I argue that slam poets theatrically channel (out)rage against conservative Brahminical attitudes that treat articulations around women's bodies as continually verging on the pornographic, whilst obscuring how caste is implicated in sexual discourse. Finally, I argue that casteless Anglophone spoken word can be contrasted with anti-caste vernacular performances by Dalit artists who articulate possibilities for a futurist Ambedkarite castelessness.